Factors influencing the retention of participants in online cancer screening training programs in India - Kavitha Dhanasekaran; Roshani Babu; Vipin Kumar; Shalini Singh; Roopa Hariprasad (BMC Medical Education, 2020)
Abstract Background Online courses have broken the boundaries in imparting knowledge. While in western countries e-learning in medical education is well accepted, it is still an upcoming field in low- and middle-income countries like India. Attrition is a major threat to online courses world-wide. The objective of this article is to share the experiences in conducting online cancer screening courses, reasons for attrition and ways to improve retention. Methods Online training program in preventive oncology for medical professionals is being conducted since 2017, which is 14-week long with weekly one-hour sessions and specific curriculum for healthcare professionals. Since the retention of participants was a major challenge in all the courses, a short online survey was conducted to identify the reason behind quitting the course and suggestions to improve retention. The data was analyzed in November 2019. Results Among 614 enrolments, 26% (159/614) refused to attend the course and only 55% (252/455) completed the course successfully. Among the attendees 52% (238/455) were females, 71% (325/455) were from the public sector and 71% (324/455) were non-specialists. The attrition was high among non-specialists 49% (160/324), male participants 57% (124/217) and public sector doctors 52% (170/325). The main reasons for quitting the course were high workload in the health facilities 75% (52/69) and poor internet connectivity 12% (8/69). Conclusion The internet connectivity should be strengthened in all the healthcare centers to facilitate e-learning. A dedicated time-slot should be allotted to the providers for e-learning and updating their knowledge in addition to their routine work.